(untitled) (Dhaka University Journal of Science, 2012)
A general construction method of simultaneous confounding in pn ( p is prime) factorial experiment is proposed. The concept of matrix method in the construction of factorial experiment with a single factorial effect confounded is used to develop the method. The procedure may be extended for the construction of simultaneous confounding of factorial experiment with three or more factorial effects confounded. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11531 Dhaka Univ. J. Sci. 60(2): 265-270, 2012 (July)